"Kiss myAsthma": Using a participatory design approach to develop a self-management app with young people with asthma. (2nd September 2018) - Davis, SR; Peters, D; Calvo, RA; Sawyer, SM; Foster, JM; Smith, L
ABSTRACT: Objective : Young people with asthma often lack engagement in self-management. Smartphone apps offer an attractive, immediate method for obtaining asthma information and self-management support. In this research we developed an evidence-based asthma app tailored to young peoples needs, created using a participatory design approach to optimize user engagement. This paper describes the participatory design process. Methods : This multi-phased research included concept generation and ideation of app design by young people with asthma, and development of asthma information by the research team. Clinical review was sought regarding safety and accuracy of app content. Participants suggestions for improvement and any problems with the app were logged throughout. Our young co-designers were invited back to test a high fidelity prototype app using a "think aloud" process and completed a usability questionnaire. Results : Twenty asthma patients aged 15-24 years contributed to the initial app design. Three respiratory specialists and two pharmacists suggested minor corrections to clinical terminology in the app which were all incorporated. Nine co-designers acted as expert reviewers of the prototype app, of whom eight completed a usability questionnaire. Median usability scores (maximum score 6) indicated high satisfaction with app content, usefulness and ease of use [median item score 5.3 (range 4.7-6.0)]. All feedback was incorporated to create an updated prototype app. Conclusions : A clinically sound asthma app has been developed which is considered highly acceptable to the young co-designers. A six-week test of the engagement, acceptability, and usefulness of the app in young people not involved in the participatory design will follow.